Konsep Kepemimpinan Kelompok Kecil (Micro-Leadership) dalam Manajemen Pendidikan Islam - Wahyu Febriana; Binti Luthfiah; Muhammad Akmansyah (Lentera: Jurnal Ilmiah Kependidikan, 2026)
This study aims to construct the concept of micro-leadership in madrasah management based on the managerial analysis of the Hadith regarding the obligation to appoint a leader among three travelers. Using a qualitative library research method with a hadith commentary approach and organizational behavior analysis, this study finds that the hadith is not merely travel ethics but a theological foundation for forming effective functional work units. The results indicate that the principle of one leader for three people aligns with span of control and agile leadership theories, recommending the formation of small teams (3–5 members) with a single chain of command to enhance decision-making speed and accountability. The practical implication of this research offers a madrasah organizational structure model that decentralizes authority at the micro-level to overcome bureaucratic inefficiencies and ambiguity in committee responsibilities.